Co-inoculation of multi-trait plant growth promoting rhizobacteria promotes growth and nutrient assimilation of transplant Aman rice (cv. BRRI dhan49) - Phalguni Das; Protyasha Biswas; Mousumi Akter; Atiqur Rahman; Md. Shohidul Alam (Fundamental and Applied Agriculture, 2023)
BACKGROUND: Plant growth-promoting rhizobacteria (PGPR) are the rhizosphere bacteria that can enhance plant growth by a wide variety of mechanisms. This study was conducted to assess the effects of plant growth-promoting rhizobacteria on growth and nutrient assimilation of rice. METHODOLOGY: Seeds of transplant Aman rice (cv. BRRI dhan49) were collected from Bangladesh Rice Research Institute (BRRI). Pot experiment was conducted with rice plant inoculated with two PGPR isolates MQ1 (Zinc solubilizing, IAA producing, phosphate solubilizing and N2-fixing) and MQ2 (Zinc solubilizing, phosphate solubilizing and N2-fixing) with addition of three different levels of chemical fertilizers (FR0.0 no fertilizer, FR0.5 half of the recommended dose, FR1.0 full of the recommended dose of fertilizers) following Completely Randomized Design with three replications. Plant height at different days after transplanting, number of tillers hill-1 and biomass yield were recorded. Plant samples were analyzed for N, P, Ca, Mg, S, Fe, Zn, Mn, Cu and Cd contents. KEY FINDINGS: Rice plants inoculated with the PGPR both individually or in consortium along with different doses of fertilizers showed an improved plant growth and increased biomass production. Highest plant height (74.057±3.164 cm) and maximum number of tillers hill-1 (13.000±2.082) were recorded in PGPRMQ1RF1.0 treatment and the highest biomass production (10.275±0.541 t ha-1) was recorded in PGPRCONS.RF1.0. Nitrogen content and uptake of the individual PGPR treated rice plants was also found to be higher in comparison with the uninoculated control plants. Besides these iron and zinc content of the treated rice plants was also found to be higher in comparison with the uninoculated control plants. N (0.268±0.046), P (0.626±0.095), Fe (6.062094±A), Zn (1.237±0.197) and Mn (11.908±1.879) uptake were observed higher in PGPRMQ1RF1.0 treatment. CONCLUSION: PGPR inoculation has immense potential to be used as agricultural crop inoculants as they promote plant growth as well as nutrient assimilation of rice. [Fundam Appl Agric 2023; 8(3.000): 507-523]